Exploring the literature on music participation and social connectedness for young people with intellectual disability: A critical interpretive synthesis. (December 2017) - Murphy, Melissa AI; McFerran, Katrina
Background: This article explores the literature on social connectedness and music for young people with disability. It then critically examines the level of congruence between the reported literature to date and current rights-based disability studies discourse. Method: A critical interpretive synthesis was used to examine 27 articles referencing the use of music for social connectedness. Areas of focus in the review are the nature of connections being fostered in music programs, the use of voice and collaboration. Results: The majority of music programs reported on closed groups. Outdated 'expert' models of working persist. The use of participants' voice in the literature is growing, although there is a lack of collaboration and negative reporting. Conclusion: A shift in thinking heralds greater collaboration with participants, although this could be broadened to include decisions on research agendas, planning and evaluation. There is also need for active fostering of broader socio-musical pathways.